PEMANFAATAN IKAN BEONG SEBAGAI BAHAN TAMBAHAN PADA PEMBUATAN PRODUK FETTUCINI BUMBU BALI - Mahanani, Martha Widhy Tri; Harsana, Minta (Prosiding Pendidikan Teknik Boga Busana, 2021)
This research aims to; (1) Discovering the recipe and processing teachnique that is suitable for making Beong fish substitute fettucini products, (2) proximate testing as a nutritional information source for Beong fish substitution fettucini products, (3) packing and providing labels that attract customers to pasta products Beong fish subttitute fettucini, (4) calcite the selling price of Beong fish substitute fettucine pasta products, (5) knowing public acceptance of Beong fish substitute fettucine pasta products. This research is a research that uses stages of determining the product and substitution material, paling development by making products to be developed., Validation I and II by experts, limited product control tets and substitution of 30 panelists. Validator form is used as a measure of public acceptance of beong fish substitution fettucine products in term of color, aroma, texture, taste, and overall. The results of the T test in terms of color, aroma, texture, taste and overall results in control and development products were not significantly different. It can be concluded that public acceptance in this panelist test shows the assessment with the results like the product. Keywords: fettucine, beong fish, bumbu bali